Post‐Fire Sediment Yield From a Western Sierra Nevada Watershed Burned by the 2021 Caldor Fire - Amy E. East; Joshua B. Logan; Peter Dartnell; Helen W. Dow; Donald N. Lindsay; David B. Cavagnaro (Earth and Space Science)
Abstract Watershed sediment yield commonly increases after wildfire, often causing negative impacts to downstream infrastructure and water resources. Post‐fire erosion is important to understand and quantify because it is increasingly placing water supplies, habitat, communities, and infrastructure at risk as fire regimes intensify in a warming climate. However, measurements of post‐fire sediment mobilization are lacking from many regions. We measured sediment yield from a forested, heavily managed 25.4‐km2 watershed in the western Sierra Nevada, California, over 2 years following the 2021 Caldor Fire, by repeat mapping of a reservoir where sediment accumulated from terrain with moderate to high soil burn severity. Sediment yield was less than the geochronology‐derived long‐term average in the first year post‐fire (conservatively estimated at 21.8–28.0 t/km2), low enough to be difficult to measure with uncrewed airborne system (UAS) and bathymetric sonar survey methods that are most effective at detecting larger sedimentary signals. In the second year post‐fire the sediment delivery was 1,560–2,010 t/km2, an order of magnitude above long‐term values, attributable to greater precipitation and intensive salvage logging. Hillslope erosion simulated by the Water Erosion Prediction Project (WEPP) model overestimated the measured amount by a factor of 90 in the first year and in the second year by a factor (1.9) that aligned with previously determined model performance in northern California. We encourage additional field studies, and validation of erosion models where feasible, to further expand the range of conditions informing post‐fire hazard assessments and management decisions.